Venom variation in Bothrops asper lineages from North-Western South America - Mora-Obando, Diana (2020)
Bothrops asper is a venomous pitviper that is widely distributed and of clinical importance in Mesoamerica and northern South America, where it is responsible for 50–80% of all envenomations by Viperidae species. Previous work suggests that B. asper has a complex phylogeographic structure, with the existence of multiple evolutionarily distinct lineages, particularly in the inter-Andean valleys of north South America. To explore the impact of the evolutionary history of B. asper on venom composition, we have investigated geographic variation in the venom proteome of this species from the populations from the Pacific side of Ecuador and south-western Colombia. Among the 21 classes of venom components identified, proteins from mainly four major toxin families, snake venom metalloproteases (PI- and PII-SVMP), phospholipases A2 (K49- and D49-PLA2s), serine proteinases (SVSP), and C-type lectins-like (CTL) proteins are major contributors to the geographic variability in venom. Principal component analyses demonstrate significant differences in venom composition between B. asper lineages previously identified through combination of molecular, morphological and geographical data, and provide additional insights into the selection pressures modulating venom phenotypes on a geographic scale. In particular, altitudinal zonation within the Andean mountain range stands out as a key ecological factor promoting diversification in venom. In addition, the pattern of distribution of PLA2 molecules among B. asper venoms complements phylogenetic analysis in the reconstruction of the dispersal events that account for the current biogeographic distribution of the present-day species' phylogroups. Ontogenic variation was also evident among venoms from some Ecuadorian lineages, although this age-related variation was less extreme than reported in B. asper venoms from Costa Rica. The results of our study demonstrate a significant impact of phylogenetic history on venom composition in a pitviper and show how analyses of this variation can illuminate the timing of the cladogenesis and ecological events that shaped the current distribution of B. asper lineages. Biological significance: Bothrops asper, called “the ultimate pitviper” due to its defensive behavior, large body size, and medical importance, represents a species complex that is widely distributed from southern México southwards across north-western South America to north-western Perú. This work reports the characterization of the venom proteomes of B. asper lineages from the Pacific sides of Ecuador and south-western Colombia. Multivariate analyses indicate that variability in venom composition among the B. asper lineages is driven by proteins from four major toxin families, presumably in response to selection pressures created by recent and historical ecological conditions created by geological and climatic events from the Pliocene-Pleistocene to the present along the Central and South American Continental Divide. The emerging biogeographic pattern of venom variation, interpreted in the context of the current phylogenetic hypotheses, support and complement previously proposed evolutionary Plio-Pleistocene dispersal events that shaped the present-day distribution range of B. asper lineages. In addition, our venomics data indicate the occurrence of genetic exchange between Colombian and Pacific Costa Rican populations, which may have occurred during the second wave of B. asper migration into Mesoamerica. Our work represents a foundation for a future broader sampling and more complete “-omics” analyses to deepen our understanding of the patterns and causes of venom variation in this medically important pitviper. © 2020 Elsevier B.V.